Mesenchymal Stem Cell Exosomes Promote Functional Osteochondral Repair in a Clinically Relevant Porcine Model. Issue 3 (March 2022) - Zhang, Shipin; Wong, Keng Lin; Ren, Xiafei; Teo, Kristeen Ye Wen; Afizah, Hassan; Choo, Andre Boon Hwa; Lai, Ruenn Chai; Lim, Sai Kiang; Hui, James Hoi Po; Toh, Wei Seong
Background: Previous studies have reported the efficacy of human mesenchymal stem cell (MSC) exosomes for the repair of osteochondral defects in rats and rabbits. However, the safety and efficacy of MSC exosomes remain to be validated in a clinically relevant large animal model. Purpose: To validate the safety and efficacy of human MSC exosomes for osteochondral repair in a clinically relevant micropig model. Study Design: Controlled laboratory study. Methods: Bilateral osteochondral defects (6-mm diameter and 1-mm depth) were surgically created in the medial femoral condyles in knees of 12 micropigs. The pigs then received 2-mL intra-articular injections of MSC exosomes and hyaluronic acid (HA) (Exosome+HA) or HA alone after surgery and thereafter at 8 and 15 days. Osteochondral repair was assessed by magnetic resonance imaging (MRI) at 15 days and at 2 and 4 months after surgery as well as by macroscopic, histological, biomechanical, and micro—computed tomography (micro-CT) analyses at 4 months after surgery. Results: Exosome+HA–treated defects demonstrated significantly better MRI scores than HA-treated defects at 15 days and at 2 and 4 months. Additionally, Exosome+HA–treated defects demonstrated functional cartilage and subchondral bone repair, with significantly better macroscopic and histological scores and biomechanical properties (Young modulus and stiffness) than HA-treated defects at 4 months. Micro-CT further showed significantly higher bone volume and trabecular thickness in the subchondral bone of Exosome+HA–treated defects than that of HA-treated defects. Importantly, no adverse response or major systemic alteration was observed in any of the animals. Conclusion: This study shows that the combination of MSC exosomes and HA administered at a clinically acceptable frequency of 3 weekly intra-articular injections can promote functional cartilage and subchondral bone repair, with significantly improved morphological, histological, and biomechanical outcomes in a clinically relevant porcine model. Clinical Relevance: Our findings provide a robust scientific rationale to support a phase 1/2 clinical trial to test MSC exosomes in patients with osteochondral lesions.